Estudo descritivo do suicídio no município de São Paulo (Brasil) - 1959 a 1968 A descriptive study of suicide in the county of S. Paulo (Brazil) from 1959 to 1968 - Victório Barbosa (Universidade de São Paulo, 1974)
Foi feito estudo epidemiológico retrospectivo descritivo de mortalidade por suicídio no município de São Paulo, Brasil, baseado nos dados oficiais. Foram estudadas as tendências de alguns caracteres epidemiológicos dessa causa de morte nos anos de 1959 a 1968: causas exógena, distribuição cronológica, distribuição causal e distribuição por sexo e idade. Based in the official data it was made an epidemiological retrospective descritive study about the mortality caused by suicide in the county of S. Paulo, Brazil. This study also includes the trends of some epidemiological characters for this couse of death, from 1959 to 1968, which are: exogenous causes, chronologic distribution, monthly distribution and distribution in sex and age.